Peran Citra Merek dalam Memoderasi Pengaruh Kualitas Layanan dan FOMO terhadap Minat Menabung Generasi Z di Bank Syariah Indonesia (BSI) - Kayla Fildzah KD; Friska Anggi Siregar; Nanda Safarida (Universitas Islam Negeri Sumatera Utara, 2026)
This study aims to examine the role of brand image as a moderating variable in the influence of service quality and Fear of Missing Out (FOMO) on savings interest in Indonesian Islamic banks. Using a quantitative approach and a sample of Islamic bank customers, this study analyzes how good service quality and perceived FOMO contribute to savings interest, as well as how brand image strengthens or weakens this relationship. The results show that service quality and FOMO have a significant influence on savings interest, with brand image acting as a moderator that strengthens the positive effect of service quality on savings interest, while significantly moderating the impact of FOMO. These findings provide important implications for Islamic banks' marketing strategies in building a strong brand image to increase customer loyalty and savings interest.